Service Engineering: Linking Business and IT. - Margaria, Tiziana; Steffen, Bernhard (Computer (00189162), 2006)
The article explores open-world software in the realm of business processes. The authors argue for the application of service-oriented design that has long driven the telecommunications infrastructure development and applications development. Because of its strong emphasis on modularization, development of service-oriented software radically alters the way business processes are modeled, realized, and maintained. The complex functions of the underlying business applications are virtualized by domain-specific services so that they can be loosely coupled to form transorganizational processes. They suggest new tools to guarantee a vertically seamless development of the modeled process.